Therapeutic Validation of Venous Pulsatile Tinnitus and Biomaterial Applications for Temporal Bone Reconstruction Surgery Using Multi-sensing Platforms and Coupled Computational Techniques - Hsieh, Yue-Lin; Gao, Xiuli; Wang, Xing; Hsiang, Fu-Chou; Sun, Xinbo; Wang, Wuqing (Frontiers in Bioengineering and Biotechnology, 2022)
The application of grafts and biomaterials is a cardinal therapeutic procedure to resolve venous pulsatile tinnitus (PT) caused by temporal bone dehiscence during transtemporal reconstructive surgery. However, the transmission mechanism of venous PT remains unclear, and the sound absorption and insulation properties of different repair materials have not been specified. This study quantifies the vibroacoustic characteristics of PT, sources the major transmission pathway of PT, and verifies the therapeutic effect of different material applications using joint multi-sensing platforms and coupled computational fluid dynamics (CFD) techniques. The in vivo intraoperative acoustic and vibroacoustic characteristics of intrasinus blood flow motion and dehiscent sigmoid plate of a typical venous PT patient were investigated using acoustic and displacement sensors. The acoustical, morphological, and mechanical properties of the dehiscent sigmoid plate, grafts harvested from a cadaveric head, and other biomaterials were acquired using acoustical impedance tubes, micro-CT, scanning electron microscopy, and mercury porosimetry, as appropriate. To analyze the therapeutic effect of our previous reconstructive techniques, coupled CFD simulations were performed using the acquired mechanical properties of biomaterials and patient-specific radiologic data. The peak in vivo intraoperatively gauged, peak simulated vibroacoustic and peak simulated hydroacoustic amplitude of PT prior to sigmoid plate reconstruction were 64.0 dB, 70.4 dB, and 72.8 dB, respectively. After the solidified gelatin sponge-bone wax repair technique, the intraoperative gauged peak amplitude of PT was reduced from 64.0 dB to 47.3 dB. Among three different reconstructive techniques based on CFD results, the vibroacoustic and hydroacoustic sound were reduced to 65.9 dB and 68.6 dB (temporalis-cartilage technique), 63.5 dB and 63.1 dB (solidified gelatin sponge technique), and 42.4 dB and 39.2 dB (solidified gelatin sponge-bone wax technique), respectively. In conclusion, the current novel biosensing applications and coupled CFD techniques indicate that the sensation of PT correlates with the motion and impact from venous flow, causing vibroacoustic and hydroacoustic sources that transmit via the air conduction transmission pathway. The transtemporal reconstructive surgical efficacy depends on the established areal density of applied grafts and/or biomaterials, in which the total transmission loss of PT should surpass the amplitude of the measured loudness of PT.